Gêneros de atividade: a face oculta do trabalho docente evidenciada em um texto de instrução ao sósia - Modolo, Soelene de Fátima Brovoski (2019)
This research aims to analyze the characteristics of the genres of teaching activity identified in an instruction to the double of a language teacher of basic education, as well as to investigate the stylization processes evidenced in her teaching practice, in order to identify possible stylistic retouching in the genres of activity. Following a Bakhtinian dialogic perspective and a Vygotskian development, this study is based on theoretical-methodological contributions of the Work Sciences, in special the Ergonomic Activity ones (FERREIRA, 2000, 2008; GUÉRIN et al., 2001; AMIGUES, 2004; SAUJAT, 2004) and the Clinic of Activity ones (FAÏTA, 2002; CLOT, 2006a, 2006b, 2007, 2010a, 2010b; RUELLAND-ROGER, 2013; CLOT; FAÏTA, 2016) and on theoretical-methodological assumptions of Socio-discursive Interactionism (MACHADO, 2004, 2007; BRONCKART, 2006, 2007, 2012; MACHADO; BRONCKART, 2009). To complement the analyses, the assumptions of the discourse analysis of French line are also used (MAINGUENEAU, 1997a; 1997b; 2011; 2015). The data includes a text generated from an instruction to the double with a language teacher of the basic education of the state network of the southwestern region of Paraná. It is part of texts produced by researchers from audio recordings with views to the interpretation of the acting in texts about the teaching work (BRONCKART, 2006) and integrates a database linked to the project of Muniz-Oliveira (2014). The results show that the implied common evaluations regulate personal activity in an implicit way. They are related to different aspects of teaching work: role of the teacher in the teaching-learning process; lesson time management; expected behaviors of students in each class (year); difficulties in working with certain content/ ability; among others. In the processes of stylization, it is possible to notice the presence of several retouches in the activity genres that the teacher has in her practice, so that it is the teacher's gestures that convert the instruments of the "other" into "her" instruments. This occurs through a phenomenon called functional migration, within a regulatory activity (LIMA, 2010a, 2010b, 2014, 2017), in which the teacher seeks to meet contradictory needs at the same time, given the conflicts of criteria that are present in her daily life. In this way, this study shows that the complexity of the teaching activity is not only related to the multiple tasks of the teacher, which involve other "others" and several instruments. Rather, it points out that this complexity is related to the nomadism (migration) of the elements of the teaching work. It clarifies that an explanation of the genres of activity, in the sense of contributing with teachers in formation or even with those who may be in difficulty, must take into account the processes of stylization, the retouches added to the genres of activity, in situation.